Pengembangan Usaha Ekonomi Kreatif Keripik Pisang Ditinjau Dari Perspektif Ekonomi Islam (Studi Pada Usaha Keripik Pisang Di Desa Tanjung Bunut Kecamatan Belida Barat) - Yudi Rudi; Dedi Siswanto; Undiana Putri (Kafalah: Jurnal Ekonomi, Manajemen, dan Keuangan Syariah, 2026)
The purpose of this study is to find out the development of the creative economic business of banana chips and to find out the development of the creative economic business of banana chips from an Islamic economic perspective. Field research is essentially a method to find out specifically and realistically what is happening at a certain time in society. From this research, it can be understood that this research is a qualitative field where research is conducted to regularly study the background and development of the creative economic business of banana chips. Based on the results of research and discussion regarding the development of the Banana Chips industry in Tanjung Bunut Village, West Belida District in an Islamic Economic Perspective, it can be concluded that in developing the industry, the owners of the Banana Chips industry in Tanjung Bunut Village, West Belida District, use diversification strategies and intensive strategies. In an Islamic Economic perspective, the Banana Chips industry in Tanjung Bunut Village, West Belida District, in its operations has implemented five main elements in management, namely Planning, Organizing, Actuanting, Controlling and Leading